2017
DOI: 10.1080/10715762.2017.1307979
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of hepatocyte function with free radical generators and reparation or prevention with coffee polyphenols

Abstract: Liver diseases are linked in the majority of cases to oxidative stress that antioxidants could neutralize with reducing liver injury. Chlorogenic acid, a coffee polyphenol, possesses antioxidant prosperities. The aim of this study was to evaluate in vitro preventive and corrective effects of cholorogenic acid in hepatocyte toxicity induced by free radicals. Hepatocytes were isolated from adult male Wistar rats. To determine corrective effects and reparation, cells were first exposed to two free radical generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The relative oxidation stress levels in MHs cultured in the APAP-MHs, [TA + (APAP-MHs)], and [TA + (APAP-MHs) + TA] groups were 100% ± 5.4%, 94% ± 5.3%, and 89% ± 3.2%, respectively ( Figure 3 D), suggesting that 1 μg/mL of TA not only slightly prevents oxidative stress before toxicity but also reduces oxidative stress after cell toxicity significantly. This finding aligns with that of a previous study [ 23 ] that reported the antioxidative effects of TA, indicating that it reduces oxidative stress and free radical damage.…”
Section: Resultssupporting
confidence: 93%
“…The relative oxidation stress levels in MHs cultured in the APAP-MHs, [TA + (APAP-MHs)], and [TA + (APAP-MHs) + TA] groups were 100% ± 5.4%, 94% ± 5.3%, and 89% ± 3.2%, respectively ( Figure 3 D), suggesting that 1 μg/mL of TA not only slightly prevents oxidative stress before toxicity but also reduces oxidative stress after cell toxicity significantly. This finding aligns with that of a previous study [ 23 ] that reported the antioxidative effects of TA, indicating that it reduces oxidative stress and free radical damage.…”
Section: Resultssupporting
confidence: 93%
“…The protective effects of coffee are postulated due to multiple ingredients. Phenolic acids and caffeine may directly impact liver carcinogenesis via inhibiting proliferation of HCC cells, suppressing progression of HCC and preventing oxidative damage to hepatocytes [42][43][44]. It is also postulated that coffee reduces insulin resistance and improves glucose metabolism which may also play a role in slowing the progression of liver disease [45].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds such as phenolic acids 27,28 and caffeine 29 have also been shown to have chemopreventive properties, including in liver carcinogenesis 38 . These compounds have been shown to inhibit the proliferation of HCC cell lines in vitro and suppress the progression of HCC in vivo 30 , while chlorogenic acid has been shown to prevent oxidative damage in hepatocytes 31 . Instant coffee, in comparison with ground and decaffeinated coffee, has been demonstrated to have higher levels of those biochemical compounds 3,4 , which therefore could partly explain the more marked reduced risk of HCC in our study.…”
Section: Discussionmentioning
confidence: 99%